The Influence Of Electronic Word Of Mouth Information On Social Media On Game Top Up Purchase Intentions - Baghas Basyu Nondho (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the influence of Electronic Word of Mouth (eWOM) on social media on consumer purchase intention for game top-ups. A total of 177 respondents who actively play games and use social media completed a questionnaire, which was analyzed using SmartPLS 3 with purposive sampling techniques. The results showed that Information Quality, Information Credibility, and Needs of Information had a significant positive effect on Information Usefulness. Information Usefulness also had a significant positive effect on Information Adoption, and Information Adoption had a significant positive effect on Purchase Intention. However, Information Task Fit and Attitude Toward Information did not have an effect on Information Usefulness. The findings of this study are expected to contribute to digital marketing strategies in the gaming industry, particularly regarding the use of eWOM to enhance consumer purchase intention.